Vibration Sensor Approaches for the Monitoring of Sand Production in Bohai Bay - Kai Wang; Zhiguo Liu; Gang Liu; Longtao Yi; Kui Yang; Shiqi Peng; Man Chen (Shock and Vibration)
The real-time monitoring of sand production has always been an important issue during the process of oil production in offshore field. This paper illustrates a new alternative vibration sensor approach to monitor the sand production. A special broadband sensor was selected. Then the time-frequency analysis, characteristic sand frequency band filter method, and peak searching-denoising method were proposed to enhance the detection ability of sand vibration signals in strong background noises of crude oil flow. After that, visible differences in time-frequency domain and power spectrum between sand and nonsand production well can be observed. Four typical wells in Bohai oil production platform were selected to investigate the monitoring effects of sand production. The monitoring findings show that there exists a good correlation between the vibration power spectrum amplitude and the sand production volume, which is consistent with actual results.